Commercialization unsustainable to Himalayan environment - Singh, Gopal S. (Ecological Questions, 2013)
Indigenous people of north western Himalayan region of India utilize a wide range of biological resources for subsistence. The age-old practices of resource utilization have supported the rural economy with equity and social justice and conservation of resources since generations. However, in recent times, due to market demand, the biological resources are subjected to premature and frequent harvesting of ruthless exploitation by unskilled people particularly from outskirt of people. In addition to this, unfavorable government forest policy and ignoring people’s participation in decision-making and changing climatic conditions are some of the prime factors responsible for changing traditional resource management practices. Over increasing population pressure demand lead for market oriented commercial demand has resulted in over-exploitation of some of the plant resources at alarming pace. This calls for the development of resource management techniques built up on traditional knowledge capable of meeting the challenges of conservation on the one hand and socio-economic development of the local people on the other. Changing indigenous resource management practices in north western Himalaya imperils herbal based health care system and livelihood pattern.